Pod rozsadzonym kamieniem - Kaczmarek, Jarmila E. (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2012)
Among the ‘hoards’ unearthed between the second half of the 19th and the first half of the 20th century, there is a particular collection of items found under erratic boulders. Wielkopolska produced nine such discoveries, dated to the Eneolithic (Bytyń, the district of Szamotuły), the Bronze or Early Iron Ages (Brzezie, the district of Pleszew; Kaczory, the district of Piła; Łuszkowo, the district of Kościan; Rosko, the district of Czarnków-Trzcianka), as well as the early Middle Ages (Górzno, the district of Leszno; Magnuszewice, the district of Jarocin; Nojewo, the district of Szamotuły; Słuszków, the district of Kalisz). Similar finds are also known from other regions of Poland. The ‘hoards’ were buried near or under boulders. In the Bronze and Early Iron Ages the deposits consisted of various bronze and iron items, while in the medieval times they predominately consisted of silver. The practice of burying objects under boulders were most probably related to some cult rituals. In the ancient times, the cult of boulders, interpreted i.e. as places where epiphany of gods took place, was quite common; hence burying precious offerings under boulders. In the early Middle Ages boulders were regarded as one of the borders between the known and unknown world, thus the deposition of precious objects in such places was supposed to ensure their usage in future life. In Poland, the cult of boulders was still present in the nineteenth century. Folk legends told stories of boulders, sometimes of treasures found underneath, for which an archetype might have been provided by particular discoveries of objects buried under boulders in prehistory. However, cult rituals cannot account for all finds – the context of each find must be always taken into consideration.
Under a burst stone